Current Trends in Plant Disease Diagnostics and Management Practices - Kumar, Pradeep; Gupta, Vijai Kumar; Tiwari, Ajay Kumar; Kamle, Madhu (Fungal Biology, 2016)
Plant diseases play an important role on our daily lives. Most of plant diseases are visible and are caused by biotic and/or abiotic factors. Symptoms are usually the results of a morphological change, alteration or damage to plant tissue and/or cells due to an interference of the plant's metabolism. All basic structures of vascular plants are subject to attack by pathogens. The failure in accurate disease diagnosis and management may lead to huge losses in plant production and related commodities, which causes nutritional food scarcity. Typically, the appearance of a biotic symptom will indicate the relatively late stage of an infection and/or colonization of a pathogen. Expert detection, accurate diagnosis, and timely management play a significant role in keeping plants free from pathogens. In this book expert scholars share their research knowledge and key literature which are vital toward the diagnosis of plant diseases across the globe, addressing traditional plant pathology techniques, as well as advanced molecular diagnostic approach.